Management Effectiveness in Financial Institutions - Samsi, Hamdan (1997)

(untitled)
Management is the process of achieving organizational goals by engaging in the 4 major functions of planning, organizing, leading and controlling. Management practices and styles is an ongoing activities and are still evolving. Changes in technology, international affairs, business practices and organizational social responsibilities are causing managers "to reexamine their methods and goals as well as place increased emphasis on innovation. In Malaysia, management practices in Malaysia are still an subject open for study and discussion. Malaysian people which consisted of heterogeneous ethnic groups has to a large extent influence the management practices in today's Malaysian organization.